Answer:
See below
Explanation:
Considering
, then
![\Vert \vec{u} \cdot \vec{v}\Vert \leq \Vert\vec{u}\Vert \Vert\vec{v}\Vert$ we have $(\vec{u} \cdot \vec{v})^2 \leq (\vec{u} \cdot \vec{u})(\vec{v} \cdot \vec{v}) \quad$](https://img.qammunity.org/2022/formulas/mathematics/high-school/35aneq706n3seuukmceow0gdkn89bu1bki.png)
This is the Cauchy–Schwarz Inequality, therefore
![$\left(\sum_(i=1)^(n) u_i v_i \right)^2 \leq \left(\sum_(i=1)^(n) u_i \right)^2 \left(\sum_(i=1)^(n) v_i \right)^2 $](https://img.qammunity.org/2022/formulas/mathematics/high-school/8ikadvk7qm55x3hsts777fmgnkdn5v5oix.png)
We have the equation
![(\sin ^4 x )/(a) + (\cos^4 x )/(b) = (1)/(a+b), a,b\in\mathbb{N}](https://img.qammunity.org/2022/formulas/mathematics/high-school/psiitrrls4syaba90zv7hr7yv0xqc1uoiw.png)
We can use the Cauchy–Schwarz Inequality because
and
are greater than 0. In fact,
. Using the Cauchy–Schwarz Inequality, we have
![(\sin ^4 x )/(a) + (\cos^4 x )/(b) =((\sin^2 x)^2)/(a)+((\cos^2 x))/(b)\geq ((\sin^2 x+\cos^2 x)^2)/(a+b) = (1)/(a+b)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zqwp9v8nuh3bhbkilwg4gs6m78myw8h4jx.png)
and the equation holds for
![\frac{\sin^2{x}}{a}=\frac{\cos^2{x}}{b}=(1)/(a+b)](https://img.qammunity.org/2022/formulas/mathematics/high-school/owsjmfg19bals2lb8doz32yxrjltkwrmi5.png)
![\implies\quad \sin^2 x = (a)/(a+b) \text{ and }\cos^2 x = (b)/(a+b)](https://img.qammunity.org/2022/formulas/mathematics/high-school/sysd9b3r6td09r47rp3dp38vnp9mwisvn0.png)
Therefore, once we can write
![\sin^2 x = (a)/(a+b) \implies \sin^(4n)x = (a^(2n))/((a+b)^(2n)) \implies(\sin^(4n)x )/(a^(2n-1)) = (a^(2n))/((a+b)^(2n)\cdot a^(2n-1))](https://img.qammunity.org/2022/formulas/mathematics/high-school/m8btm9chffg0go4p9t2vpu5qyf3m5xrkpg.png)
It is the same thing for cosine, thus
![\cos^2 x = (b)/(a+b) \implies (\cos^(4n)x )/(b^(2n-1)) = (b^(2n))/((a+b)^(2n)\cdot b^(2n-1))](https://img.qammunity.org/2022/formulas/mathematics/high-school/g7uvycy4by0p6m6njuwys7m0muwzurv442.png)
Once
![(a^(2n))/((a+b)^(2n)\cdot a^(2n-1))+ (b^(2n))/((a+b)^(2n)\cdot b^(2n-1)) =(a^(2n))/((a+b)^(2n) \cdot (a^(2n))/(a) ) + (b^(2n))/((a+b)^(2n)\cdot (b^(2n))/(b) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/h9tof18ayxprr3p44e2mrcqu0d3ex6p01z.png)
![=(1)/((a+b)^(2n) \cdot (1)/(a) ) + (1)/((a+b)^(2n)\cdot (1)/(b) ) = (a)/((a+b)^(2n) ) + (b)/((a+b)^(2n) ) = (a+b)/((a+b)^(2n) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/tjwb808mj5q555rmuem7oy2o4o01lfi8yg.png)
dividing both numerator and denominator by
, we get
![(a+b)/((a+b)^(2n) ) = (1)/((a+b)^(2n-1) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/5po3ppmv2t1t3pc8l2pnn61bn1ga322lpw.png)
Therefore, it is proved that
![(\sin ^(4n) x )/(a^(2n-1)) + (\cos^(4n) x )/(b^(2n-1)) = (1)/((a+b)^(2n-1)), a,b\in\mathbb{N}](https://img.qammunity.org/2022/formulas/mathematics/high-school/80zdlhsepbz0wt9vcpwllckwz6t23xk72s.png)